Influence of Flame Retardants on Flammability of Cellulose-Based Material - Nguyen, Hoang Chung; Bui, Thi Thanh Nga; Nguyen, Trung Thanh (Old Journal, 2019)
This work aims to investigate the application of fire retardant agents in production of fire-proof cellulose-based material. Several agents are used including boron compounds, and ammonium polyphosphate/ diatomite composite filler. The results show that when using a mixture of boric acid and sodium borax at the ratio of 1:1 for impregnation of paper, the combustion speed of paper is reduced significantly. On the other hand, synthesized ammonium polyphosphate/ diatomite filler also provides good flame resistance to the paper when it is used as a filler. The use of composite filler supported by a retention aid like cationic starch seems to be less effective than the impregnation method.